2010
DOI: 10.1016/j.geothermics.2009.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic waterfrac stimulation to develop an Enhanced Geothermal System (EGS)—Conceptual design and experimental results

Abstract: The design and results of a cyclic hydraulic fracturing experiment performed to enhance the productivity of the geothermal research well at Groß Schönebeck (Germany) are presented. The stimulation carried out in the low-permeability volcanics of the Lower Rotliegend (Lower Permian) included alternating stages with cyclic changes of low and high flow rates with up to 150 L/s over six days in conjunction with the addition of quartz sand to support fracture opening. There was rapid water level increase in an adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 25 publications
(32 reference statements)
3
64
0
1
Order By: Relevance
“…Low enthalpy geothermal reservoir rocks (see Zimmermann et al, 2009a, Zimmermann andReinicke, 2010, for details) are to be found here as siliciclastic sediments and volcanics of the lower Permian at an average depth of about 4000 m and at formation temperatures of up to 150°C. The existing well EG was used for repeated stimulation treatments to investigate scenarios of enhancing productivity of thermal fluid recovery from the underground (Zimmermann et al 2009b).…”
Section: Site Descriptionmentioning
confidence: 89%
See 1 more Smart Citation
“…Low enthalpy geothermal reservoir rocks (see Zimmermann et al, 2009a, Zimmermann andReinicke, 2010, for details) are to be found here as siliciclastic sediments and volcanics of the lower Permian at an average depth of about 4000 m and at formation temperatures of up to 150°C. The existing well EG was used for repeated stimulation treatments to investigate scenarios of enhancing productivity of thermal fluid recovery from the underground (Zimmermann et al 2009b).…”
Section: Site Descriptionmentioning
confidence: 89%
“…The sensor is located at only 500 m distance to the injection point providing the opportunity to monitor induced seismicity as low as M W~-2.0. (Zimmermann et al, 2009a, Zimmermann andReinicke, 2010), at maximum well-head pressures of 49.5 MPa and 38.0 MPa, respectively. In the following analysis we primarily focus on the major injection in volcanic rocks.…”
Section: Site Descriptionmentioning
confidence: 97%
“…According to the literature, the average highest flow rate achieved during stimulation is 97 L/second (s) (36.6 barrels [bbl]/minute [min]) (Asanuma et al 2004;Michelet and Toksöz 2006;Zimmermann et al 2009). Fuel consumption was determined by using the average highest flow rate and from industry input.…”
Section: Hydraulic Stimulation Of the Resourcementioning
confidence: 99%
“…This method has been widely used in energy industry to enhance the recovery of hydrocarbons from tight reservoir rocks, through the creation of hydraulic fractures and coupling of these new higher permeability flow paths with the natural fracture networks in the rock (Fu et al, 2013;Wang, 2015). In addition, hydraulic fracturing can be applied in fields of the disposal of radioactive waste in the underground spaces (De Laguna et al, 1968), heat production from hot dry rock geothermal reservoirs (Zimmermann et al, 2009(Zimmermann et al, , 2010, as well as the measurement of in-situ stresses (Fairhurst, 2003;Haimson and Cornet, 2003;Yokoyama et al, 2014).…”
Section: Introductionmentioning
confidence: 99%